Estrategias para la disminución del impacto ambiental de los vehículos eléctricos fabricados con materiales convencionales (2017)
Currently and after the great development of new clean energy technologies, as well as the need to have a healthy world and the agreement reached by the countries attending the conference in Rio in 1992 for the reduction of gas emissions of greenhouse effect, the development of electric vehicle technology that was proposed at the beginning of the invention of automobiles was returned, but its development was stopped due to the production costs of these.